KOMPOSISI ASAM LEMAK DAN BILANGAN IOD MINYAK DARI SEMBILAN VARIETAS KELAPA SAWIT DxP KOMERSIAL DI PPKS - Sujadi Sujadi; Hasrul Abdi Hasibuan; Hernawan Yuli Rahmadi; Abdul Razak Purba (Pusat Penelitian Kelapa Sawit, 2016)
Nine different oil palm commercial planting materials which are: DxP La Mé, DxP Yangambi, DxP Simalungun, DxP Marihat, DxP PPKS 239, DxP PPKS 540, DxP PPKS 718, DyxP SP1 (Dumpy) and DxP Langkat were analyzed for their fatty acid composition and Iodine Value (IV).Their dried mesocarp crude palm oil (CPO) content were observed between 63.3 – 88.5%, with DxP Yangambi had the highest (83.2 ± 5.3%) and significantly different compared to the rest of the varieties. DxP Simaungun had the highest palmitic acid (47.8 ± 2.1%), while DxP La Me had the highest oleic acid (44.3 ± 2.9%) and both were significantly different from the other varieties. Nevertheless, other fatty acid content in the CPO were not significantly different between varieties. IV in the CPO was not significantly different between varieties, with DxP PPKS 540 and DxP La Mé had the highest with 56.5 ± 2.0 Wijs and 55.6 ± 2.6 Wijs respectively, while DxP Simalungun had the lowest IV with 50.1 ± 2.2 Wijs. Palm kernel oil (PKO) content between varieties was not significantly different and gave number between 44.1 – 56.0%. The main fatty acid component in the PKO were lauric acid (44.3 ± 49.7), myristic acid (14.0 ± 17.7), oleic acid (14.4 ± 19.7) and palmitic acid (7.6 ± 9.4). Most of the fatty acid composition of the PKO were not significantly different betwen varieties, except for the myristic acid content of the DxP PPKS 718. No significant different also observed on the IV of the PKO between varieties, with DxP Marihat had the highest (21.6 ± 1.6 Wijs) and DxP La Mé had the lowest (19.6 ± 2.3 Wijs).